PEtab: interoperable specification of parameter estimation problems in systems biology - Schmiester, Leonard; Schälte, Yannik; Bergmann, Frank T.; Camba, Tacio; Dudkin, Erika; Egert, Janine; Fröhlich, Fabian; Fuhrmann, Lara; Hauber, Adrian L.; Kemmer, Svenja; Lakrisenko, Polina; Loos, Carolin; et al. (PLoS Computational Biology, 2021)
Reproducibility and reusability of the results of data-based modeling studies are essential. Yet, there has been—so far—no broadly supported format for the specification of parameter estimation problems in systems biology. Here, we introduce PEtab, a format which facilitates the specification of parameter estimation problems using Systems Biology Markup Language (SBML) models and a set of tab-separated value files describing the observation model and experimental data as well as parameters to be estimated. We already implemented PEtab support into eight well-established model simulation and parameter estimation toolboxes with hundreds of users in total. We provide a Python library for validation and modification of a PEtab problem and currently 20 example parameter estimation problems based on recent studies.
Gesehen am 09.04.2021